Implementation of Using Small Group Method to Improve Speaking Skill - Muhammad Husein Ali; Mutmainnah Mustofa; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This article aims at knowing about implementation, result, advantages and disadvantages of small group method. The teaching and learning process is a core part of the school environment, both in the classroom and outside the classroom. In this case there needs to be a creative teacher, who is able to invite students to follow the learning well. The learning process can happen between teachers and students, and students with students. The research design in this study is a qualitative research. With this kind of qualitative research descriptive. The subject of this study is 36 students and the researcher used interview to some students in this research. in this study to obtain the required data is divided into several phases. First, the researcher approached the principal as the leader, and the English teacher. Secondly, researcher pre-observation the environment around school. Third, do observations, interviews, documents related to research and so on. In this case act of researcher as planners, implementers, data collection, analysts, data commentators, and research results reporters. The findings in my research are small group activities that are applied in this school to improve students ' speaking skills by inviting students to better fight their shyness in interacting with English. Speaking English is not an easy thing, so students should practice again to improve their skills. Key Words: Implementation, Improve, Small Group Method, Speaking Skill.